2016
DOI: 10.1016/j.jvs.2014.11.074
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent neuroprotection of delta-opioid peptide [D-Ala 2 , D-Leu 5 ] enkephalin on spinal cord ischemia-reperfusion injury by regional perfusion into the abdominal aorta in rabbits

Abstract: These data revealed that regional administration of DADLE through the abdominal aorta provided dose-dependent protection on spinal cord I/R in rabbits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…The median number of viable α-motor neurons at 48 h after reperfusion was 3.5 (range, 2–4) in the D per group, which was significantly higher than the median value of 0.5 (range, 0–1) in the NS group (corrected P=0.0060), but lower than the median value of 7 (range, 5.25–7) in the Sham group (corrected P=0.0018). The results of the Tarlov scores and histopathological examination of the spinal cords of the rabbits that received DADLE were consistent with a previous study (15).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The median number of viable α-motor neurons at 48 h after reperfusion was 3.5 (range, 2–4) in the D per group, which was significantly higher than the median value of 0.5 (range, 0–1) in the NS group (corrected P=0.0060), but lower than the median value of 7 (range, 5.25–7) in the Sham group (corrected P=0.0018). The results of the Tarlov scores and histopathological examination of the spinal cords of the rabbits that received DADLE were consistent with a previous study (15).…”
Section: Resultssupporting
confidence: 91%
“…The model of 30 min aortic occlusion in rabbits was established, as previously described (15,17). Briefly, under general anesthesia, the femoral arteries of the rabbits were exposed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite intensive efforts to develop new neuroprotective agents for experimental central nervous system ischemia models, most so far have failed to show clinical effects. Our previous studies showed that DADLE could attenuate spinal cord I/R injury during the ischemic period and the neuroprotective effect appeared most significant at a dose of 0.05 mg/kg (Liu et al, 2016 ). Antioxidative and antiapoptotic properties of DADLE were only reported in vitro experiments or in the model of cerebral I/R injury (Tsao et al, 1998 ; Hayashi et al, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…The model of spinal cord ischemia was established as described previously (Liu et al, 2016 ). In brief, an incision was made in the right iliac region and the right femoral artery was exposed.…”
Section: Methodsmentioning
confidence: 99%